老齡化背景下長期照護的現實選擇: 基於儒家倫理觀的思考: What is Proper Long-term Care for the Elderly? A Confucian Ethical Reflection - JIANG, Lanshu; ZHOU, Ling; REN, Ran (International Journal of Chinese & Comparative Philosophy of Medicine, 2010)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 中國邁入老齡化國家之後，失能老人的長期照護將會成為未來養老問題中的難點。失能老人作為病患的權利需要靠社會的福利制度來得以維繫，這在目前中國福利制度仍未十分健全的情況下是很難實現的。本文將通過對中國儒家倫理觀的思考，吸取其精華，探索老齡化背景下符合中國國情的長期照護發展之路。 According to the standard set by the United Nations, if more than 10% of the population of a society is over 60 years old, then that society qualifies as an aging society. This means that China has been an aging society since 2000. Currently, China has one hundred and forty-nine million people over 60 years old, of which more than thirty million require long-term care to various degrees. 8% of elderly rural Chinese are unable to afford institutional long-term care, even if such institutional care is available. Obviously, China faces grave challenges in providing long-term care for its ever-increasing elderly population. Unfortunately, Chinese bioethics has failed to conduct careful research on these challenges to develop appropriate Chinese public policy on long-term care. This essay offers a Confucian ethical approach to the issue and proposes a series of policy recommendations framed in terms of Confucian ethical concerns. As is well known, Confucian ethics places great emphasis on the virtue of filial piety (xiao) on the part of children, who are expected to respect and take care of their elderly parents. It is the Confucian view that elderly people should, insofar as is possible, live at home, with the assistance of their children, and lead their elderly lives among their children and grandchildren. Living in an institution with other elderly people is not considered a normal, much less ideal, human living environment. This essay argues that this Confucian value should be preserved in contemporary Chinese society. This requires proper policy formulation and governmental contributions. First, in moral education, the Confucian virtue of filial piety and familial interdependence, rather than individual independence, should be promoted. Second, the government should provide financial incentives and awards to children who choose to stay home to take care of their elderly parents or grandparents. Finally, based on the Confucian virtue of beneficence (ren), the government should offer special assistance to families with seriously disabled elderly members. People should also be encouraged to organize volunteer groups to offer help to needy families. In short, the Confucian moral principle of reciprocity (“do not impose on others what you would not want others to do to you”) suggests that if we do not want to be abandoned by our children and by society when we become old, it is high time for us to act and set appropriate long-term policies. DOWNLOAD HISTORY | This article has been downloaded 935 times in Digital Commons before migrating into this platform.